2020
DOI: 10.1186/s12883-020-01938-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of active group-based dance, singing, music therapy and theatrical interventions for quality of life, functional communication, speech, motor function and cognitive status in people with Parkinson’s disease

Abstract: Background Parkinson’s disease (PD) is a common neurodegenerative condition associated with a wide range of motor and non-motor symptoms. There has been increasing interest in the potential benefit of performing arts as a therapeutic medium in PD. While there have been previous reviews, none have considered all performing arts modalities and most have focused on dance. This systematic review examined the potential benefit of all active group-based performing arts interventions for quality of li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 118 publications
(173 reference statements)
2
37
0
2
Order By: Relevance
“…The over-arching theme to emerge from this trial was that online therapeutic dancing has impact and is enjoyable, safe and feasible for people in the early stages of PD. In agreement with global studies showing the benefits of ‘face to face’ dancing for people with chronic progressive neurological conditions, 20,39-43 the participants in this study reported that online dance therapy enabled them to connect with others and engage in structured physical activity that was of benefit to health and well-being.…”
Section: Discussionsupporting
confidence: 88%
“…The over-arching theme to emerge from this trial was that online therapeutic dancing has impact and is enjoyable, safe and feasible for people in the early stages of PD. In agreement with global studies showing the benefits of ‘face to face’ dancing for people with chronic progressive neurological conditions, 20,39-43 the participants in this study reported that online dance therapy enabled them to connect with others and engage in structured physical activity that was of benefit to health and well-being.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, PD-Ballet can decrease social isolation and improve quality of life,22 with participants highly motivated and viewing PD-Ballet as an important part of their lives 27. Equally, while recent systematic reviews and studies on the effects of performing acts modalities (including dance and ballet) reported promising benefits on Parkinson’s symptoms45 46 very few RCTs have investigated the benefits of ‘dance’ in both motor and non-motor symptoms, pointing to the need for this research.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Hierbei wird eine rhythmische Stimulation, meist durch ein Metronom, zur therapeutischen Manipulation der Sprechrate genutzt. Auch für die Behandlung der Dysarthrophonie bei Parkinson kommt das therapeutische Singen zur Anwendung [23]. Für das Atemtraining nutzen Musiktherapeuten einfach zu handhabende Blasinstrumente wie Melodika, Mundharmonika und Kazoo.…”
Section: Sprache Und Sprechenunclassified